The Effect of Gender Composition on Perceptual Accuracy: a Three-Level Approach Using Dyadic Data - Castro, Erin D. (American journal of criminal justice, 2020)
Emerging evidence that perceptual measures of peer deviance typically used in criminology may be inaccurate has resulted in recent investigations into the factors that condition misperception. Studies find that lower levels of self-control and lack of time spent with friends contribute to misperception, while friendship closeness increases accuracy. One unexplored factor that has been shown to impact peer-to-peer interactions is gender. Filling in this gap, the current study explores how gender structure in combination with friendship quality and individual levels of self-control, may cause differences in the perceptual accuracy of peer deviance among friendship pairs. Using item-response-based mixed-effects models, results demonstrate that women in female-only friendships produce the most accurate perceptions of peer deviance. Men in male-only friendships produce the least accurate perceptions. Since men are typically self-report greater engagement in deviant behavior than women, this finding highlights that peer deviance perceptions are most flawed among people who are engaging in the most deviance. Additionally, higher quality friendships have more accurate perceptions while those who have less self-control are markedly less accurate. Implications for feminist research and peer deviance measurement are reviewed.